Conduction Mechanism in Polyaniline -Polyacrylic Acid Blend - Hesham A.Saleh; Nadhim A.Abdullah; Hameed A.hamdi; Wael. A. S. Abdul Ghafor (College of Education for Pure Sciences, 2009)
Abstract: The electrical properties of polyaniline-polyacrilic acid blend are reported using Al/Polymer/Al structured. The D.C. conductivity is measured in the temperature range (23-70) C˚ via two probe method. The current was measured at steady state conditions. The domains conduction mechanism was identified as Ionic conduction. The D.C conductivity and the activation energy were estimated to be 5.7x10-11 (Ω.cm)-1 while activation energy is (1.3 eV), and dark DC bulk conductivity of blend was observed to increase orders of magnitude in the investigated temperature range.